Analysis of Factors Related to HIV Incidence in Tanimbar Islands Regency - Veronika Maria Barbara Aryesam; Suryadi Nicolaas Napoleon Tatura; Windy M. V. Wariki (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
HIV is an infectious disease that is the leading cause of death with a high mortality rate, high morbidity rate and requires long-term diagnosis and therapy.UNAIDS data shows that HIV in 2017 was 1.8 million people, in 2018 1.7 million people, and in 2019 1.7 million people. Data from the Tanimbar Islands Regency Health Office in 2022 the number of HIV positive patients was 30 people, in 2023 the number of HIV positive patients was 40 people and in 2024 the number of HIV positive patients was 80 people. This study aims to analyze the relationship between knowledge, attitudes and behavior with the incidence of HIV in the Tanimbar Islands Regency. The type of research used isqualitative approach by looking at case studies on HIV Incidents to analyze factors related to HIV incidents in Tanimbar Islands Regency in October-December 2024. The population and sample in this study were 25 HIV-positive patients and key informants, namely the Hospital Director, Head of the Medical Records Room. Research Results The data collected from informants on the questions asked by the researcher were 25 respondents but the researcher only wrote representatives of several respondents, because out of 25 respondents almost all respondents responded to the researcher well and politely. And in accordance with the results of the recordings and the results of the attached notes. The results of the study from various respondents for one purpose, namely to find out what factors are related to HIV incidents in Tanimbar Islands Regency, especially at the dr. PP Magretti Saumlaki Regional Hospital. For families or closest people as well as the Hospital and health workers, it is hoped that they will always provide support, educational attention and assistance so that people with HIV remain enthusiastic and also to prevent transmission.